Perlindungan Hukum Terhadap Konsumen Pengguna Jasa Ekspedisi Pengiriman Barang (Studi Pada Pt. J&T Kota Ambon) - Surachim, Muhammad Oghan; Pesulima, Theresia Louize; Pariela, Marselo Valentino Geovani (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: J&T is an industry that provides goods delivery services both in the form of documents and packages. J&T is a new industry that utilizes IT in providing its services, with the advantage of providing goods and services so that customers do not need to come to the J&T office when they want to send and receive goods. Sometimes delivering goods is not always easy, for example, goods agreed upon by both parties have been sent but do not arrive at the destination address, goods arrive late, are lost or damaged during the delivery process. The research method used in this research is normative juridical, normative juridical research is legal research (legal search) which is carried out to find the truth of coherence, this writing focuses on literature study which means more research and study of existing and applicable legal regulations. In general PT. J&T is a technology-based delivery company that provides goods and document delivery services to all areas covered by PT. J&T is included in Ambon City. Service users only need to pay a certain amount of money to PT. J&T as a fee for sending goods to the specified address. However, in every delivery of goods, of course there are several problems found during the shipping and delivery process which cause losses for consumers. In this case PT J&T Ambon does not fulfill the rights of consumers, such as in the case of consumer rights which are not fulfilled because the goods delivered do not reach the hands of consumers. The issue of consumer protection is not solely an individual problem, but is actually a collective and national problem because basically everyone is a consumer. As users of goods delivery services, consumers need to obtain legal protection in order to protect their interests. Seeing this situation, the government issued a policy regulating consumer rights through law to protect consumer interests in consuming goods and/or services. This government policy is regulated in the UUPK.